(untitled) (Comprehensive Journal of Science, 2025)
Background: The increasing prevalence of antimicrobial resistance among clinically relevant bacterial pathogens underscores the need for effective plant-derived antibacterial agents. Ziziphus spina-christi (Sidr) and Retama raetam are traditionally used medicinal plants known to contain phenolic and flavonoid compounds with potential antimicrobial properties. Aim: This study aimed to comparatively evaluate the antibacterial activity of ethanolic extracts of Z. spina-christi and R. raetam against Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae using the standardized disc diffusion method. Methodology: Bacterial inocula standardized to 0.5 McFarland were tested using the Kirby–Bauer disc diffusion assay on Mueller–Hinton agar. Three defined concentrations of each plant extract were applied to sterile discs, along with solvent controls and a reference antibiotic. After incubation at 37°C for 18–24 h, the inhibition zones were measured in millimeters. Data were analyzed using one-way analysis of variance (ANOVA) and appropriate post hoc tests. Results: A clear concentration-dependent antibacterial effect was noted. Higher extract concentrations produced significantly larger inhibition zones for all bacterial species. Z. spina-christi extract demonstrated greater antibacterial potency than R. raetam, particularly against S. aureus, while both extracts inhibited E. coli and Klebsiella to varying degrees. Conclusion: The ethanolic extracts of Z. spina-christi and R. raetam exhibited promising antibacterial activity, supporting their potential use as complementary natural antibacterial agents. Further MIC/MBC studies and phytochemical analysis are recommended.